THE INFLUENCE OF PROFITABILITY, DIVIDEND POLICY, EARNINGS PER SHARE, AND AGENCY COSTS ON THE FIRM VALUE - Trisandi Eka Putri; Tiara Puspitasari (Sekolah Tinggi Ilmu Ekonomi Sutaatmadja, 2024)
This research aims to determine the Influence of Profitability, Dividend Policy, Earnings Per Share, and Agency Costs on the Firm Value of Food and Beverage Companies Listed on the Indonesia Stock Exchange and Malaysia Stock Exchange from 2020 to 2022. The independent variables in this study are Profitability, Dividend Policy, Earnings Per Share, and Agency Costs, while the dependent variable is the firm's value. This research is quantitative in nature. The population of this study includes all companies in the food and beverage industry sector listed on the Indonesia Stock Exchange and the Malaysia Stock Exchange. The sampling technique used is documentation and literature study, making the entire population of the study the research sample, resulting in 27 food and beverage companies as the research sample. The sampling technique employed is purposive sampling. Data processing is carried out using SPSS25 software. This research utilizes descriptive statistical analysis, multiple linear regression analysis, classical assumption tests, and hypothesis testing. Based on the research test results, it is found that: 1. Profitability, in partial, does not have a significant influence on firm value. 2. Dividend policy, in partial, has a significantly positive influence on firm value. 3. Earnings per share, in partial, do not have a significant influence on firm value. 4. Agency costs, in partial, have a significantly positive influence